LITHUANIAN BIBLIOPHILIA IN THE SOVIET PERIOD: HISTORIOGRAPHICAL ASPECT - LIEPAITĖ, INGA (Knygotyra, 2013)
The article aims to disclose scientific or other professed evaluations of Lithuanian bibliophilia in the Soviet period. The research basis consists of historiographical literature. Exiguous historiography of the subject may be divided into two stages: 1) until 1990 and 2) after 1990. Works published in the first stage provides information on the conception of bibliophilia of that time, its origins, and historical development and the atmosphere in which it had functioned. Usually authors of the latter works declared about an ostensibly newly formed socialistic bibliophilia and its changed social and cultural functions. More significant and numerous evaluations of bibliophilia of the said period have been traced from the second half of the eight decade. This tendencymay be explained by the fact that starting from the establishment of Voluntary Society of Book Lovers of Lithuanian SSR in 1974 an organized movement of book lovers emerged which of itself motivated raising issues related to book and solving them, and at the same time encouraged to rethink the conception of the bibliophilia and its tasks. Among more important authors of bibliophilia interpretations we may distinguish two public figures: Vladas Žukas and Levas Vladimirovas.Until 2008–2012, when the author of these lines started the research of Lithuanian bibliophilia in the Soviet period, and generalized its results in several scientific and science popular publications as well as in her doctoral dissertation, there have been no considerate or special scientific evaluations devoted specifically to this phenomenon. It may be maintained that after regaining Lithuanian independence certain evaluations were based on reflections of generalcharacter, personal experience or even on presentiments, more rarely – on unpublished or published sources. Authors of the said period had a more or less negative preconceived attitude towards bibliophilia and its activities in the Soviet period. Bibliophilia was reviewed passingly in its separate specific layers. Solving general issues of Lithuanian bibliophilia history, theory, methodology and organization we not rarely touch bibliophilia of the Soviet period. Within eyeshot of researchers most often emerge Vilnius Mažvydas and Plungė Daukantas Book Lovers Clubs which played an important role in the history of Lithuanian bibliophilia and which have been continuing their activities up to the present. In other cases we limit ourselves to brief description of general state of bibliophilia or its assessment which usually consists of several sentences or paragraphs, traditionally negative, sometimes unfavourable conditions for bibliophilia development are accentuated.Further development of the research of Lithuanian bibliophilia in the Soviet period will depend on accessibility to new sources and potentialitiesthey could provide as well as research capacities.
Keywords: ...